PEMBELAJARAN DI LUAR KELAS DENGAN PENDEKATAN PEMECAHAN MASALAH BERSAMA UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN PEMAHAMAN KONSEP LINGKUNGAN - Sari, Kartika (UNIVERSITAS MUHAMMADIYAH METRO, 2010)
Lacking of laboratory facilities, methods, and media which are not involving students, have made studentsâ knowledge far away from the real problems. We can solve it by doing the off class study so students can be active and solve their problems together. This researchâs aims are to get the empirical images of study process quality increasing and study achievement increasing in Science by doing the off class study with together problem solving approximation. This research has been done at Muhammadiyah Elementary School of Metro in the first semester of study academic year 2006/2007. The subjects are the 3rd grade students. It has been done in two cycles with Mc Kernen method. The basic competence that has been researched is how to differ the health and unhealthy environments. Time schedule are 5X2X30 minutes for two cycles. The steps are planning, acting, monitoring, and reflecting. The results showed: a. The off class study has increased the positive activities of the students and decreased the negative ones; their motivation were growing as well as their learning qualities; andÂ b. There are increasing of Science results which are shown by the higher results of the studentsâ post tests that has been held between 1st and 2nd cycles. From this research, we can suggest that: a. To do the off class study needs analytical ability of outside potency as learning source with the concept that we want to reach; b. We need more time to select the environment, analyze its strengths and weaknesses, also anticipate the problems that that may occur; c. Teachers have to get close to their students so they can be more interactive in order to get higher cognitive, affective, and psychomotor aspects.Â Kata kunci: Pembelajaran luar kelas, peningkatan motivasi, pemahaman konsep